-8+(-4)-(-3)+6-10=X

Simple and best practice solution for -8+(-4)-(-3)+6-10=X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+(-4)-(-3)+6-10=X equation:


Simplifying
-8 + (-4) + -1(-3) + 6 + -10 = X
-8 + -4 + -1(-3) + 6 + -10 = X

Multiply -1 * -3
-8 + -4 + 3 + 6 + -10 = X

Combine like terms: -8 + -4 = -12
-12 + 3 + 6 + -10 = X

Combine like terms: -12 + 3 = -9
-9 + 6 + -10 = X

Combine like terms: -9 + 6 = -3
-3 + -10 = X

Combine like terms: -3 + -10 = -13
-13 = X

Solving
-13 = X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1X' to each side of the equation.
-13 + -1X = X + -1X

Combine like terms: X + -1X = 0
-13 + -1X = 0

Add '13' to each side of the equation.
-13 + 13 + -1X = 0 + 13

Combine like terms: -13 + 13 = 0
0 + -1X = 0 + 13
-1X = 0 + 13

Combine like terms: 0 + 13 = 13
-1X = 13

Divide each side by '-1'.
X = -13

Simplifying
X = -13

See similar equations:

| 2/5b+3=-11 | | (X/8)-(3/4)=(9/16) | | t(7+2)-4= | | 5-2x=40 | | 3.5n+3.5n+11n=180 | | 7r+1=50 | | 16=6.5n-2.4(2n-5) | | 5(a-4)=3a+2 | | 3=-6x+6x | | 25x-2=13 | | 36=c+5 | | -8x-94=77+x | | 10n-8=36 | | 144=3(5x+8) | | 3x-18=-63 | | -8+(-4)-(-3)+6-10= | | -3(-2n)=63 | | 3x+18/6x | | 3.5n=11n | | 23+18u=21+14u | | (x/2)+(3/4)=(7/4) | | 10x+(10500/x)+100=0 | | -3x+17+5x=11+2(x+3) | | (-3x^3+5x^2+11x)-(6x^2-11x+7)+(5x^3+7x-11)= | | a+14=bfora | | 6+9(x-12)= | | 126*47/63*1/4 | | 19-(4m+5)=5+3m-12 | | f(x)=15(-3)+4 | | 7/2+2x=13 | | 7(y-8)+24=2(y-6) | | -20=6(6x+5)+19x |

Equations solver categories